Zircon U–Pb geochronology from the Paraná bimodal volcanic province support abrief eruptive cycle at ~135 Ma - Pinto, V.; Hartmann, L.; Santos, J.; McNaughton, Neal; Wildner, W. (Elsevier Science BV, 2011)
Ion microprobe U–Pb isotopic data on zircons from the Paraná magmatic province are presented from one tholeiitic (high-Ti Pitanga type) and three felsic volcanic rocks from the low-Ti Palmas and high-Ti Chapecó types. Igneous zircons from the four volcanic rocks yield volcanism ages within error: i.e. 134.4 ± 1.1 Ma (basalt), 134.6 ± 1.4 Ma (rhyodacite), 134.8 ± 1.4 (quartz latite) and 135.6 ± 1.8 Ma (quartz latite). The age of Paraná magmatism based on previous Ar–Ar geochronology has two divergent ranges: 1) 1 to 2 million years with magmatic peak at 131–133 Ma, and 2) over ~ 10 m.y. between 137 and 127 Ma. Our results show that the bimodal volcanics of the province, at least to the south of the Piquiri lineament, have very high effusion rates over a brief period with a main pulse at ~ 135 Ma, about 2% older than proposal 1, more akin to a short period of magmatism. These results are most significant for the understanding of time relations in this large intraplate magmatic province.